Antibacterial activity of 5-chloro substituted phenyl n-acylhydrazone derivatives with aromatic substitution at meta- and para- directors as potential adjuvants - Long, Yi Xian (2024)
The rise of antibiotic-resistant bacterial strains has imposed the exploration for the compounds that is new in order to enhance the antibacterial efficacy for food safety, animal health as well as human clinical settings. This research investigates the antibacterial properties of 5-chloro substituted phenyl Nacylhydrazone (NAH) derivatives, with a focus on derivatives featuring aromatic substitutions at meta- and para-positions as potential adjuvants. A total of 9 NAH derivative compounds were tested against a range of bacteria individually as well as in combination with ciprofloxacin, streptomycin and chloramphenicol as adjuvants, including Bacillus cereus (ATCC 13061), Bacillus subtilis subsp. spizizenni (ATCC 6633), Staphylococcus. aureus (ATCC 6538), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), Salmonella Typhimurium (ATCC 14028), Methicillin-resistance Staphylococcus aureus (ATCC 33591) and Methicillin-resistance Staphylococcus aureus (ATCC 43300), to assess their effectiveness. Both minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were identified through a broth microdilution assay to determine antibacterial activity. Compound 1 (3,4-Cl2) obtained MIC values with the range of 3.91‒31.25 μg/mL which demonstrated a broad spectrum of antibacterial activity. In contrast, NAH derivative compounds with the substitution of CH3, F, OCH3 and H demonstrated specific-species antibacterial activity against S. aureus (ATCC 6538), characterized by MIC value of 62.50 μg/mL. When combined with standard antibiotics, particularly ciprofloxacin, the NAH derivatives exhibited synergistic effects, significantly enhancing bactericidal activity against B. cereus (ATCC 13061), B. subtilis subsp. spizizenni(ATCC 6633) and Methicillin-resistant S. aureus (ATCC 33591). However, the combination of NAH derivatives with chloramphenicol did not produce a bactericidal effect, as indicated by the lack of a minimum bactericidal concentration (MBC) value. This suggested a predominantly inhibitory rather than lethal interaction. Furthermore, the fractional inhibitory concentration (FIC) index calculations showed that streptomycin-adjuvant combinations considered did not exhibit significant interaction, whereas combinations including adjuvant compound 2 and 9 displayed antagonism against B. subtilis subsp. spizizenni(ATCC 6633). Overall, most of the antibiotic-adjuvants combinations showed indifference in their interaction with the selected bacteria. Hence, it is not recommended for further study of these antibiotic-adjuvant combinations